Peran Pemerintah Terhadap Pekerja Yang Dirumahkan Pada Masa Pandemi Covid-19 - Rahman, Rahman (Mahesa Research Center, 2023)
The World Health Organization (WHO) stated that today the world is experiencing a Global Pandemic due to the emergence of Corona Virus Disease 2019 (Covid-19). The current situation has affected the society which causes casualties and impacts the socio-economic conditions with a decrease in employment. The government plays an important role in overcoming the problems arising from this situation, especially concerning unpaid leave employees. This study employs a normative legal approach with qualitative data analysis to discuss the role of the government amidst the Covid-19 pandemic dealing with unpaid leave employees. Referring to the Circular Letter from the Minister of Labor to the Leaders of Companies throughout Indonesia Number SE-907/MEN/PHI-PPHI/X/2004 concerning the Prevention of Termination of Mass Employment item F, it is stated that unpaid leave is classified as one of the efforts that can be taken before terminating employment. The absence of derivative regulations that regulate the issue of unpaid leave employees has weakened the position of employees to get their rights. The government has tried several efforts to solve the problems relating to unpaid leave, such as by providing incentive assistance, job training, and other social assistance. The findings indicate that the government, in carrying out their duties and functions, should construct new regulations concerning unpaid leave employees as a preventive measure for upcoming future preparation.